2009
DOI: 10.1038/ijir.2009.41
|View full text |Cite
|
Sign up to set email alerts
|

Yohimbine relaxes the human corpus cavernosum through a non-adrenergic mechanism involving the activation of K+ATP-dependent channels

Abstract: The mechanism by which yohimbine relaxes the human corpus cavernosum remains unclear. Using the human corpus cavernosum strips immersed in isometric baths containing Krebs-Henseleit solution, this study investigates the effect of yohimbine on the relaxation of the human corpus cavernosum through nitrergic pathways involving the activation of ATP-dependent potassium channels (K ATP ). The maximal relaxation induced by yohimbine in the human corpus cavernosum strips pre-contracted with phenylephrine was 100±0% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Several studies have documented that K channel modulators, putative activators of the K ATP channel, elicit a concentrationdependent relaxation of isolated human corporal smooth muscle (Andersson, 1992. Although activation of the K ATP channel has been suggested to be involved in the action of yohimbine (Freitas et al, 2009), phentolamine (Silva et al, 2005) and testosterone (Yildiz et al, 2009) on cavernosal tissue, the importance of this contribution to the total effects of these agents on erectile mechanisms has not been established.…”
Section: B K ϩ Channelsmentioning
confidence: 99%
“…Several studies have documented that K channel modulators, putative activators of the K ATP channel, elicit a concentrationdependent relaxation of isolated human corporal smooth muscle (Andersson, 1992. Although activation of the K ATP channel has been suggested to be involved in the action of yohimbine (Freitas et al, 2009), phentolamine (Silva et al, 2005) and testosterone (Yildiz et al, 2009) on cavernosal tissue, the importance of this contribution to the total effects of these agents on erectile mechanisms has not been established.…”
Section: B K ϩ Channelsmentioning
confidence: 99%
“…Furthermore, it is already known yohimbine acts directly in blocking α-1-adrenergic receptors, decreasing the synthesis of IP3 and releasing Ca 2+ causing muscle relaxation (Hodges & Sparks, 2013). Studies also suggest that yohimbine acts in the muscle relaxation of human cavernous tissue by nonadrenergic pathway, probably activating the nitrergic soluble guanylate cyclase (NO-SGC) via and KATP (Freitas, et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Sulfonylurea drugs are commonly used to treat diabetes. However, these drugs also increase erectile dysfunction (Freitas et al, 2009). No epidemic research was found on whether the incidence of erectile dysfunction increases in patients using glibenclamide.…”
Section: Discussionmentioning
confidence: 99%